Educational analysis of the impact of Hegel's thought on art with an approach to the romanticist movement in academic textbooks in the field of art - Nima Ghasemi Dehaghi (Universidad de Cienfuegos, 2020)
The aim of this study is analyzing educational of the impact of Hegel’s thought on art with an approach to the romanticist movement in academic textbooks in the field of art. Hegel was one of the most important German idealist philosophers who presented a new understanding of (aesthetics) in (art). From Hegel's perspective, each work of art consists of two parts: 1- The (spiritual) meaning 2- The (physical) form aspect. For this reason, this adaptation itself rises the basic types of art. In fact, the basic character (Romantic Art) is already provided and the (spirit) transcends (matter) and becomes an independent being. In this research, we seek to find new modes of expanding the aesthetic in the realm (art) by approaching art in the period of (romanticism) and getting assistance from (aesthetically) Hegel's perspective. The result is that if we call the work (art) beautiful since its creator is the (spirit) human being, it can be far superior to nature's yield. Hence, in his aesthetics, Hegel also discusses beauty and natural beauty, as he thinks the worst of human contemplation result is superior to nature, because there is always (the spirit), freedom and presence of the artist. So, (beauty) only benefits from the source of the ultimate truth and testifies to it.